LANGUAGE ACQUISITION UNRAVELED: NEW INSIGHTS INTO PSYCHOLINGUISTICS - Silitonga, Sarah Priscilla; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2024)
This journal entry explores the intricate processes of language acquisition through the lens of psycholinguistics, integrating recent advancements in cognitive science, neuroscience, and computational linguistics. It examines traditional theories such as generative grammar, connectionism, and usage-based models, and evaluates their relevance in light of contemporary research. The discussion extends to the impact of age, cognitive abilities, and digital communication on language learning, providing a comprehensive understanding of how humans acquire and process language.